Do fund size, style, and rating explain performance? / Jacob M Ongaki - M Ongaki, Jacob (Universiti Teknologi MARA, 2021)
The purpose of this quantitative investigation was to examine whether performance (1-Year, 3-Year, and 5-Year annual returns) differences exist among fund categories by size and style (large-cap growth, large-cap blend, mid-cap growth, and small-cap growth) and fund ratings (5-Star and 4-Star) controlling covariate variables (standard deviation, turnover rate, and top-10 holding) of the United States equity MFs. Morningstar Inc. provided an insightful measure of fund performance annual returns and fund efficacy ratings. The study utilized the Analysis of Covariance and Multivariate Analysis of Covariance methods. The investigation revealed that the large-cap growth fund category produced superior annual returns than other fund families. The five-star-rated funds performed better than the four-star-rated funds. Turnover and top-10 percentage asset holdings had a statistically significant effect on fund annual performance. Investors and asset managers should consider the fund style, size, fund ratings for making short-term, medium, and long-term financial investment decisions.